Co-extrusion of piezoelectric ceramic fibres - Ismael Michen, Marina (Schriftenreihe des Instituts für Keramik im Maschinenbau - IKM, 2011)
The present work successfully developed a methodology for fabricating lead zirconate titanate [PZT] thin solid- and hollow-fibres by the thermoplastic co-extrusion process. The whole process chain, that includes: a) compounding, involving the mixing of ceramic powder with a thermoplastic binder, b) rheological characterizations, c) preform composite fabrication followed by co-extrusion,d) debinding and, finally,e) sintering of the body to near full density, is systematically described.